2017
DOI: 10.1021/jacs.7b07392
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Metal–Organic Frameworks for Dialing-in the Binding and Programming the Release of Drug Molecules

Abstract: We report the control of guest release profiles by dialing-in desirable interactions between guest molecules and pores in metal-organic frameworks (MOFs). The interactions can be derived by the rate constants that were quantitatively correlated with the type of functional group and its proportion in the porous structure; thus the release of guest molecules can be predicted and programmed. Specifically, three probe molecules (ibuprofen, rhodamine B, and doxorubicin) were studied in a series of robust and mesopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
150
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(152 citation statements)
references
References 35 publications
0
150
0
2
Order By: Relevance
“…Recent development has shown that flexibility and multivariate nature of MOFs enable researchers to better control the drug release in a highly controllable and programmable manner . For example, a recent report on MTV‐MIL‐101(Fe) indicates the controllable drug release could be achieved by well tuning interactions between drug molecules and pore environment in MTV‐MOFs . The high stability and tunability of MOF structures promise the future of MOFs as nanocarriers for controlled drug delivery.…”
Section: Properties and Applicationsmentioning
confidence: 99%
“…Recent development has shown that flexibility and multivariate nature of MOFs enable researchers to better control the drug release in a highly controllable and programmable manner . For example, a recent report on MTV‐MIL‐101(Fe) indicates the controllable drug release could be achieved by well tuning interactions between drug molecules and pore environment in MTV‐MOFs . The high stability and tunability of MOF structures promise the future of MOFs as nanocarriers for controlled drug delivery.…”
Section: Properties and Applicationsmentioning
confidence: 99%
“…This exponential growth has been underpinned, to some extent, on the thorough quest of rational design strategies to build/functionalize -in a controlled manner -MOFs with predetermined dimensionalities and topologies, [11][12][13] and the possibility to use X-ray crystallography to follow and rationalize the proposed synthetic methodology. [14][15][16] These have enable MOFs to find applications in such diverse fields as gas adsorption and separation, [17][18][19][20] catalysis, 21,22 molecular recognition processes, 23,24 drug delivery, 25,26 magnetism 27,28 and water remediation. [29][30][31] However, this has not been the case for MOFs constructed from one-dimensional (1D) rod-like Secondary Building Units (SBUs).…”
mentioning
confidence: 99%
“…MOFs have been proposed as an attractive alternative to mitigate drawbacks that other drug delivery systems (DDSs) face, as they can exhibit low toxicity, good clearance, high drug loadings, and are easy to functionalise, yet examples of MTV‐MOFs for drug delivery applications are still limited . The coordination modulation (CM) protocol—in which monotopic ligands (modulators) compete with the MOF linkers for metal cluster coordination sites during synthesis—has been widely studied to control physical properties such as size, crystallinity, colloidal dispersion, stability and porosity (through defect chemistry), while we have recently shown that it can be used to control MOF surface chemistry and functionality .…”
Section: Introductionmentioning
confidence: 99%